2022
DOI: 10.3390/su14052859
|View full text |Cite
|
Sign up to set email alerts
|

Returns to Disease Resistance Research When Pest Management Is an Option

Abstract: Resistant cultivars offer a pathway to sustainable intensification by maintaining yields and reducing inputs in the face of disease pressure. Past studies of economic returns to crop breeding research for disease resistance measured farm-level benefits, by comparing yields for improved resistant varieties (RVs) to susceptible traditional varieties. This approach will poorly approximate actual research benefits if non-RV pest management options exist, because it does not account for farmer pest control behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…However, this does not imply that consumers did not benefit; they benefited from improved tuber quality, continuous and increased supply, and stable prices (Maredia et al, 2000). The findings are consistent with Mooney et al (2022), who found that consumers did not realize benefits through price changes but the total benefits of bean-resistant varieties combined with pest management technologies in Northern Ecuador.…”
Section: Economic Surplus Estimatessupporting
confidence: 56%
“…However, this does not imply that consumers did not benefit; they benefited from improved tuber quality, continuous and increased supply, and stable prices (Maredia et al, 2000). The findings are consistent with Mooney et al (2022), who found that consumers did not realize benefits through price changes but the total benefits of bean-resistant varieties combined with pest management technologies in Northern Ecuador.…”
Section: Economic Surplus Estimatessupporting
confidence: 56%
“…Because plant genetic resistance is not the only option available to farmers for disease control, clear articulation of the costs and benefits of effective plant genetic resistance, relative to alternatives, is critical for placing value on resistance stewardship practices. For example, using an economic model which accounts for costs of pesticide inputs, Mooney et al [44] have shown that failure to account for input costs spent on alternative disease control options underestimates the benefits of genetic resistance.…”
Section: Box 2 Economic Approaches For Non-market Valuations To Value...mentioning
confidence: 99%
“…In addition to direct effects on yield loss, effective plant genetic resistance can generate other direct and indirect economic benefits, although these are rarely recognized (figure 1). For example, beyond directly reducing yield losses, effective genetic resistance can increase food supply by lowering production costs [44,45]. Effective plant genetic resistance can also impact food supply by avoiding social concerns about reductions in food quality and safety resulting from increased reliance on pesticides [46][47][48].…”
Section: (A) the Economic Value Of Effective Genetic Resistancementioning
confidence: 99%
See 2 more Smart Citations